Current and Future Disease Burden From Ambient Ozone Exposure in India. Issue 11 (13th November 2018) - Conibear, Luke; Butt, Edward W.; Knote, Christoph; Spracklen, Dominick V.; Arnold, Stephen R.
Abstract: Long‐term ambient ozone (O3 ) exposure is a risk factor for human health. We estimate the source‐specific disease burden associated with long‐term O3 exposure in India at high spatial resolution using updated risk functions from the American Cancer Society Cancer Prevention Study II. We estimate 374, 000 (95UI: 140, 000–554, 000) annual premature mortalities using the updated risk function in India in 2015, 200% larger than estimates using the earlier American Cancer Society Cancer Prevention Study II risk function. We find that land transport emissions dominate the source contribution to this disease burden (35%), followed by emissions from power generation (23%). With no change in emissions by 2050, we estimate 1, 126, 000 (95UI: 421, 000–1, 667, 000) annual premature mortalities, an increase of 200% relative to 2015 due to population aging and growth increasing the number of people susceptible to air pollution. We find that the International Energy Agency New Policy Scenario provides small changes (+1%) to this increasing disease burden from the demographic transition. Under the International Energy Agency Clean Air Scenario we estimate 791, 000 (95UI: 202, 000–1, 336, 000) annual premature mortalities in 2050, avoiding 335, 000 annual premature mortalities (45% of the increase) compared to the scenario of no emission change. Our study highlights that critical public health benefits are possible with stringent emission reductions, despite population growth and aging increasing the attributable disease burden from O3 exposure even under such strong emission reductions. The disease burden attributable to ambient fine particulate matter exposure dominates that from ambient O3 exposure in the present day, while in the future, they may be similar in magnitude. Key Points: The disease burden associated with ozone exposure in India is larger using updated risk functions relative to earlier risk functions Stringent emission controls offset part of the increasing future disease burden from ozone exposure caused by population aging and growth The present‐day disease burden from ambient PM2.5 exposure dominates ambient O3, while in the future, they may be similar in magnitude